THE EFFECT OF TEACHER COMMUNICATION ABILITY AND LEARNING MOTIVATION ON STUDENT LEARNING OUTCOMES IN ECONOMIC LESSONS FOR CLASS XI IPS SMA EKASAKTI IN PADANG ACADEMIC YEAR 2015/2016 - Ebit Bimas Saputra (LPPM Ekasakti University, 2022)
This research was motivated by the problem of the low learning outcomes of Economics subjects of class XI Social Sciences at SMA Ekasakti Padang, where 42.11% got learning outcomes under the Minimum Completeness Criteria, namely 78 with a range of 0-100. The purpose of the study was to reveal the influence of teacher communication skills and students' learning motivation towards the learning outcomes of the Economics subject of class XI Social Sciences at SMA Ekasakti Padang. The results of data analysis show: (1) Teacher communication skills have a significant and positive effect on student economic learning outcomes at SMA Ekasakti Padang as seen from sig 0.046 < 0.05 (2) Motivation to learn has a significant and positive effect on student economic learning outcomes at SMA Ekasakti Padang. seen from sig 0.039 < 0.05. (3) Teachers' communication skills and learning motivation together have a significant and positive effect on economic learning outcomes for Ekasakti Padang High School students, as seen from sig 0.008 < 0.05. So it can be concluded that the teacher's communication ability and learning motivation affect learning outcomes, the higher the teacher's communication skills in the teaching and learning process and the better the learning motivation, the higher the learning outcomes.